Challenges Facing Sustainability in the Fashion Apparel Industry: A Literature Review and Bibliomrtric Analysis - Zuo Shuangxi, Nazlina Binti Shaari, Noor Azizi Mohd Ali, Sazrinee Zainal Abidin, Hassan Mansur Hussien, (Design Engineering, 2021)
Sustainability has been extended to a circular economy as a business development model in the fashion apparel industry. This study puts forward the concept of the knowledge, awareness, and participation of supply chain players will be critical components in the transition to a circular economy model. We identify a total of 1379 usable articles published during 2000 to 2020 from WoS and Scopus through a bibliometric analysis. Results of the bibliometric analysis show that the number of sustainable articles has generally continuously increased since 2012, sustainability in the fashion apparel industry has become increasingly popular. A few percentages of important and powerful journals that publish sustainability studies are environmental journals such as Sustainability MDPI and the journal of cleaner production. The most productive scholars are from the USA, Germany, China and UK while representative sustainable examples are the USA e-commerce platform-Rent the Runway and the UK Ellen MacArthur Foundation (EMF) that supports the circular economy. This study found the challenges facing sustainability in the fashion apparel industry and reveals its trends of study through a literature review.  It provides valuable insights for scholars of sustainability in the fashion apparel industry.